Community Based Tourism (CBT) Desa Wisata Pulesari Kabupaten Sleman - Utiya Chusna Sitapratiwi; Mohammad Muktiali (Jurusan Perencanaan Wilayah dan Kota, 2020)
Pulesari Tourism Village was inaugurated in 2012 and is an example of a tourism village that rose up after the eruption of Mount Merapi in 2010. Pulesari Tourism Village is one of the tourism villages that already apply the CBT approach in developing tourism. The development initiation of Pulesari Tourism Village was born from the local community so from the beginning of the process until the management was carried out by the local community. Now Pulesari Tourism Village is able to develop and is widely known and able to provide benefits for local community. Development of current tourism trends tends to lead on the application of Community Based Tourism (CBT), so it is interesting to examine one of the best tourism village practices that have implemented the CBT concept, namely Pulesari Tourism Village. The purpose of this study was to examine the Community-Based Tourism (CBT) of Pulesari Tourism Village and its aspects of influence. The research method used in this research is descriptive qualitative while the determination of the informant is done by non-probability sampling purposive sampling technique. As a result the development of Pulesari Tourism Village has been successful as a community empowerment and welfare improvement program because it has implemented and fulfilled the principles of CBT development in economic, social, cultural, environmental and political dimensions.